Life story work in the context of attachment-led care planning - Melanie Ferrier (Scottish Journal of Residential Child Care)
The majority of children in society are raised by their parents. This usually means that they will have had an opportunity to learn about their histories first hand by people who have raised them. Family that have been part of and shared in our lives can reminisce with us, or help us separate fact from fiction. Sometimes family provide stories of events that we can't quite remember, yet have heard so many times they become real and vivid. Yet, for many young people living in residential care, the stories of their childhood have become lost or are too painful to be shared.